1986
DOI: 10.1002/nau.1930050602
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans on the surface of the human urothelium: A preliminary report

Abstract: Glycosaminoglycans (GAGs) are thought to be present in the mucous surface coat of the human urinary bladder and to play a role in the environmental adaptation of the bladder urothelium. A defective mucous surface coat might be involved in the pathogenesis of painful bladder disease (interstitial cystitis) of unknown etiology. By a new cystoscopic scraping method for obtaining the mucous surface coat of the bladder, we investigated four painful bladder patients and three controls (prostatic hypertrophy). Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…The central premise of this postu late, that a discrete surface GAG layer is the barrier to permeability in normal urothelium [59,60], was derived primarily from animal experiments on bacterial adher ence to urothelium, involving instillation of strong irri tant chemicals into the bladder [61][62][63][64][65], Some have advo cated a qualitative rather than a quantitative change in GAG layer in IC [66][67][68], It is true that the normal urothelium of animals and man has a tenuous (60-80 nm thick) 'mucinous' surface coat that is distinctly different from glycocalyx of intes tine and can be demonstrated by appropriate special staining of light or electron microscopic preparations [69][70][71][72], Nonetheless, the postulate of deficiency of surface GAG as the primary pathogenetic factor in IC remains open to question, for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The central premise of this postu late, that a discrete surface GAG layer is the barrier to permeability in normal urothelium [59,60], was derived primarily from animal experiments on bacterial adher ence to urothelium, involving instillation of strong irri tant chemicals into the bladder [61][62][63][64][65], Some have advo cated a qualitative rather than a quantitative change in GAG layer in IC [66][67][68], It is true that the normal urothelium of animals and man has a tenuous (60-80 nm thick) 'mucinous' surface coat that is distinctly different from glycocalyx of intes tine and can be demonstrated by appropriate special staining of light or electron microscopic preparations [69][70][71][72], Nonetheless, the postulate of deficiency of surface GAG as the primary pathogenetic factor in IC remains open to question, for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…A defective barrier function of the bladder epithelium has been suggested to be involved in the pathogenesis in IC [17]. Although electron microscopic studies with Ru thenium red have failed to show differences in the mor phologic appearance of the GAG layer between patients with IC and controls [18], a recent electrophoretic study indicates differences in the biochemical composition of GAGs [19].…”
Section: Discussionmentioning
confidence: 99%
“…A study with lectin probes [19] showed that carbohydrate terminals of the bladder surface GAG are unchanged in patients with IC but that the biochemical composition of the different GAGs are altered (more galactose and fucose) in IC patients. Scraping the mucous surface coat of the bladder demonstrated further qualitative differences in the GAG composition between IC patients and controls [6]. The IC patients appeared to have a higher percentage of hyaluronic acid and dermatan sulfate than did the controls.…”
Section: Role In Interstitial Cystitismentioning
confidence: 95%